(untitled) (Journal of the College of Basic Education, 2026)
This research originates from the scientific inquiry into how a constructive critical review of previous constitutions can contribute to the process of drafting a future permanent constitution. The study operates on the premise that a critical analysis of prior constitutional experiences constitutes a practical database that can be employed in formulating a permanent constitution by building upon its strengths and avoiding its weaknesses. To ascertain the validity of this hypothesis, the historical and critical-analytical methodologies were adopted to examine a research plan focusing on the historical context of constitutional development in Syria (1920 – 2012), the similarities and differences among the successive Syrian constitutions, and the benefits of critical review for future constitutional founding. The research concluded with several key findings, most notably the potential to leverage previous Syrian constitutions by circumventing and addressing their structural deficiencies, enshrining their positive aspects represented by the preservation of positive principles and values, learning from comparative constitutional experiences, building national consensus, addressing the root causes of problems that led to constitutional crises, constructing a more flexible and sustainable system of governance, neutralizing external interference in internal affairs, and devising solutions to mitigate the gap between constitutional provisions and practical implementation. These factors collectively ensure the achievement of constitutional and political stability in Syria.